Study on the Development and Validation of Direct Spectrophotometric Method for the Estimation of Glimepiride - Chafle, Dilip M. (Current Aspects in Pharmaceutical Research and Development Vol. 4, 2021)
Aims and Objectives: To develop simple, sensitive and direct spectrophotometric methods for the estimation of widely prescribed antidiabetic hypoglycemic agent Glimepiride in pure and pharmaceutical dosage form. Application of spectrophotometric technique for development of methods. Optimization of reaction parameters and spectral characteristics for developed methods. To propose possible reaction mechanism for developed methods. Application of the developed methods for quantification of the drug in formulations. Validation of the developed method as per ICH guidelines. Methodology: Two spectrophotometric methods were developed based on ion-pair formation of drug with Cresol Red dye (Method A) and Bromophenol Blue dye (Method B) in methanol and chloroform. The possible reaction mechanism was proposed with evaluation of statistical parameters. The methods were validated for its application to determine Glimepiride in bulk as well as in pharmaceutical formulations Results: The Beer's law was found linear in the range 10 - 60 µgml-1 at 450 nm for method and 2 - 20 µgml-1 at 578 nm for method B, respectively. The linear regression equation obtained by applying least square regression analysis for glimepiride were found to be Absorbance = 0.0136 x Concentration in µgml-1 + 0.028; R2 = 0.9965 for method A and Absorbance = 0.0428 x Concentration in µgml-1 + 0.0722; R2 = 0.9949 for method B. The Sandell's sensitivity was found to be 0.0696 and 0.0177 for method A and B respectively. The apparent molar absorptivity calculated to be for both methods were 6.6724 x103 and 2.0999 x104 l mol-1 cm-1. Conclusion: Two direct spectrophotometric methods for determination of Glimepiride have been developed successfully and validated for sensitivity, accuracy, precision, repeatability and robustness as per ICH guidelines. The developed methods are suitable for the routine estimation of Glimepiride in pure and dosage form. The developed methods can act as a tool for quality control of drug in analytical laboratories.